2021
DOI: 10.1177/11769351211039862
|View full text |Cite
|
Sign up to set email alerts
|

Histone Methyltransferases Useful in Gastric Cancer Research

Abstract: Gastric cancer (GC) is one of the most frequent tumors in the world. Stomach adenocarcinoma is a heterogeneous tumor, turning the prognosis prediction and patients’ clinical management difficult. Some diagnosis tests for GC are been development using knowledge based in polymorphisms, somatic copy number alteration (SCNA) and aberrant histone methylation. This last event, a posttranslational modification that occurs at the chromatin level, is an important epigenetic alteration seen in several tumors including s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“…These findings indicated that PRDM12 expression level alterations in prostate cancer tissue samples could have a prognostic value [ 69 ]. Similarly, in a recent study, somatic copy number alterations were also found for PRDM12 in stomach adenocarcinoma samples [ 70 ]. However, currently, no studies have identified the mechanism by which PRDM12 could participate in oncogenesis.…”
Section: Exploring Novel Prdm12 Functions: Cancersupporting
confidence: 56%
“…These findings indicated that PRDM12 expression level alterations in prostate cancer tissue samples could have a prognostic value [ 69 ]. Similarly, in a recent study, somatic copy number alterations were also found for PRDM12 in stomach adenocarcinoma samples [ 70 ]. However, currently, no studies have identified the mechanism by which PRDM12 could participate in oncogenesis.…”
Section: Exploring Novel Prdm12 Functions: Cancersupporting
confidence: 56%
“…In colon and lung cancer cells, SMYD5 maintains chromosomal integrity by regulating heterochromatin and repressing endogenous repetitive DNA elements during cell differentiation [ 60 ]. SMYD5 is differentially expressed in GC, indicating that it is a potential marker for diagnosis and prognosis [ 19 , 20 ]. By constructing the SMYD-based signature and nomogram model, we confirmed that SMYDs are closely related to GC prognosis and are thus potential prognostic markers.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, high SMYD3 expression is associated with poor prognosis [ 16 , 17 ]. SMYD4 has been identified as a tumor suppressor gene in breast cancer [ 18 ], and SMYD5 may be involved in cancer and stem cell maintenance [ 19 , 20 ]. Finally, several studies have suggested the association of SMYDs with immune infiltration in breast cancer and digestive system malignancies [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Recent evidence shows that the aberrant activity of HMTs, due to amplification, deletion, or mutation of their corresponding genes, contributes to the initiation and progression of cancer. 8,13,33 Consequently, a promising strategy could target populations of patients who are carriers of these alterations. For years, it has been known that different types of cancer share common molecular mechanisms whose dysfunction allows uncontrolled cell proliferation through the deregulation or mutation of genes that positively or negatively influence the regulation of cell proliferation, migration and differentiation.…”
Section: Discussionmentioning
confidence: 99%